Analysis of Leading Vegetable Commodities in Blora Regency - Amalia, Lidya Nur (Universitas Galuh, 2024)
Each region has different potential for vegetable commodities, so a study of superior vegetable commodities in that region is needed. This research was carried out with the aim of finding out superior vegetable commodities in the sub-districts in Blora Regency. Research data is in the form of data published by the Blora Regency Central Statistics Agency. Determining superior vegetable commodities is carried out using Location Quotient (LQ). The research results show that shallots are the leading commodity in Kradenan, Bogorejo, Banjarejo and Japah Districts. Curly chilies are a superior commodity in Jiken, Bogorejo, Jepon, Tunjungan, Japah, Ngawen and Todanan Districts. Cayenne pepper is a superior commodity in the Districts of Jati, Randublatung, Kradenan, Jepon, Blora Kota and Kunduran. Tomatoes are a superior commodity in the districts of Jati, Kradenan, Jiken, Blora Kota, Japah, Ngawen and Kunduran. Petsai is a superior commodity in Kradenan and Banjarejo Districts.